2020
DOI: 10.1007/s00414-020-02406-w
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem examination of three SARS-CoV-2-positive autopsies including histopathologic and immunohistochemical analysis

Abstract: This paper describes three autopsy cases with postmortem diagnosis of SARS-CoV-2 infection, with detailed macroscopic examination as well as advanced microscopic studies of organ tissues collected using hematoxylin-eosin stains and immunohistochemical markers. Two of the cases were admitted briefly in the County Clinical Emergency Hospital of Sibiu, and one was found deceased at his home address. All three autopsies were completed at the County morgue, in the COVID-19 restricted area, using complete protective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 19 publications
2
60
0
3
Order By: Relevance
“…Twelve studies explored the presence of SARS-CoV-2 within the myocardium using different techniques ( Table 2 ) ( 8 , 9 , 17 , 19 , 23 , 24 , 29 , 30 , 39 , 41 , 44 , 48 ). In those studies, SARS-CoV-2 was detected in 50 of 105 hearts (47%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies explored the presence of SARS-CoV-2 within the myocardium using different techniques ( Table 2 ) ( 8 , 9 , 17 , 19 , 23 , 24 , 29 , 30 , 39 , 41 , 44 , 48 ). In those studies, SARS-CoV-2 was detected in 50 of 105 hearts (47%).…”
Section: Resultsmentioning
confidence: 99%
“…Myocardial ischemia, thrombosis, and cardiac dilatation were the most dominant acute findings ( Figure 2 ). Prevalence of the non-specific myocardial edema (ME) was 100% in the six studies reporting it ( 6 , 15 , 19 , 35 , 44 , 45 ). The highly prevalent chronic cardiac pathologies not only reflect the impact of cardiac comorbidities but also complicated the histopathological interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Additional COVID-19 autopsy manuscripts were identified based on the citations of these manuscripts. This resulted in 22 studies with at least two autopsies reported (Supplemental Table 1) 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 . Individual case reports were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The S2 subunit of S mediates both viral-cell fusion and cell-cell fusion [40][41][42], with cell-cell fusion readily observed both in a laboratory setting and in the lungs of SARS-CoV-2 infected patients [40][41][42][43][44][45]. To better understand the requirements and contribution of cellular proteases to S2 mediated cell-cell fusion, we performed syncytia and reporter gene assays.…”
Section: Spike Mediated Cell-cell Fusionmentioning
confidence: 99%
“…However, when S1/S2 border cleavage is blocked, viral entry can be mediated through endosomal compartments with proteolytic cleavage carried out by a member of the cathepsin family, similar to the entry pathway of SARS-CoV [10,35,[37][38][39]. In addition to promoting virus-cell fusion during viral particle entry, S can also promote cell-cell fusion, a pathogenic effect observed in the lungs of COVID-19 patients where neighboring cells fuse together to form large multi-nucleated cells, termed syncytia [40][41][42][43][44][45]. While the role of cellular proteases and S cleavage in viral entry is being extensively investigated, insight into the cleavage requirements for cell-cell fusion in SARS-CoV-2 remains more limited.…”
Section: Introductionmentioning
confidence: 99%